2019
DOI: 10.1002/ajp.23057
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cortisol levels and social behavior differ as a function of handedness in marmosets (Callithrix jacchus)

Abstract: Population hand preferences are rare in nonhuman primates, but individual hand preferences are consistent over a lifetime and considered to reflect an individual's preference to use a particular hemisphere when engaged in a specific task. Previous findings in marmosets have indicated that left‐handed individuals tend to be more fearful than their right‐handed counterparts. Based on these findings, we tested the hypotheses that left‐handed marmosets are (a) more reactive to a social stressor and (b) are slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In terms of hand preference, 50% of individuals were left-handed, 25% right-handed and 25% ambilateral. As in other studies on hand use in marmosets [ 49 , 51 53 ], we did not detect any population-level bias in hand preference. The individual hand preference was, however, highly consistent (across the time span of two years), but neither strength nor direction of hand preference were explained by individual's sex or age—a general pattern commonly reported for marmosets [ 51 53 , 55 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In terms of hand preference, 50% of individuals were left-handed, 25% right-handed and 25% ambilateral. As in other studies on hand use in marmosets [ 49 , 51 53 ], we did not detect any population-level bias in hand preference. The individual hand preference was, however, highly consistent (across the time span of two years), but neither strength nor direction of hand preference were explained by individual's sex or age—a general pattern commonly reported for marmosets [ 51 53 , 55 ].…”
Section: Discussionsupporting
confidence: 81%
“…Across studies, right-handed marmosets exhibited more explorative, active, approach-prone and less fearful behaviours than the left-handed marmosets (reviewed in [ 30 ]). Specifically, right-handed marmosets touched more objects, were faster to enter a novel room or to approach novel food [ 46 ], emitted more vocalizations when confronted with novel food [ 57 ], reacted to predator vocalizations with less freezing behaviour [ 56 ], and exhibited more social behaviours [ 53 ]. However, none of the mentioned studies directly tested the relationship between hand preference and personality measured as repeated behavioural reactions, on a broader construct level.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual decline in the strength of left-hand preference with age could also be associated with broader behavioural differences between left-handed and right-handed marmosets. Left-and right-handed marmosets differ in social behaviour: right-handed marmosets display higher levels of social interaction [33,52]. In fact, long-term records of behaviour of marmosets in our colony revealed that right-handed marmosets were more aggressive than left-handed marmosets, with the latter being recipients of more aggression and, hence, suffering more stress [53].…”
Section: Discussionmentioning
confidence: 73%
“…In common marmosets, left-handed individuals have more prolonged elevated cortisol levels, possibly indicating that they are more reactive to stress than right-handed individuals (Rogers, 2009). However, a different study reported that the basal cortisol of left-handed common marmosets was lower than that of right-handed individuals and that there is no difference in reactivity between left- and right-handed individuals (Vaughan et al, 2019). In Bonobos ( Pan paniscus ), no relationship between handedness and reactivity was found when investigating self-directed behavior and performance in cognitive tasks (Laméris et al, 2022).…”
Section: Discussionmentioning
confidence: 99%